Prioritising actions over space and time in multi-habitat ecological restoration: Insights from indicator species in coastal seascapes - Ben L. Gilby; Andrew D. Olds; Michael Sievers; Maria L. Vozzo; Brittany B. Elliott; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Ashley J. Rummell; Christopher J. Henderson (Landscape and Urban Planning, 2026)

Quantifying Environmental and Spatial Patterns of Fish on Log Snags to Optimise Resnagging in Coastal Seascapes - Lucy A. Goodridge Gaines; Jesse D. Mosman; Christopher J. Henderson; Andrew D. Olds; Hannah J. Perry; Ben L. Gilby (Estuaries and Coasts, 2024)
Long-term declines in coastal water quality and sedimentation can affect the restoration success of ecosystems such as seagrass and shellfish reefs. Resnagging coastal seascapes offers a potential alternative restoration method that is not reliant on abiotic conditions and which may enhance degraded landscapes for fish and fisheries. While common in freshwater ecosystems, such interventions are unusual for coastal seascapes despite log snags supporting significant benefits for coastal fish. In this study, we identify the spatial (e.g. seascape connectivity), habitat condition (e.g. log snag complexity and food availability) and water quality variables that best explain variation in fish assemblages on log snags to help prioritise the placement and design of resnagging efforts in estuaries. We surveyed fish assemblages on log snags using underwater videography at 363 sites across 13 estuaries in southeast Queensland, Australia, over 3 years. Sites less than 10,000 m from the estuary mouth, more than 2500 m from urban structures and located in water depths of < 3 m harboured more diverse fish assemblages. Sites less than 10,000 m from the estuary mouth with lower (< 25%) algae cover harboured greater total fish abundance and harvested fish abundance. Similar trends were found for the abundance of individuals from key functional groups, although these trends were mediated by other seascape contexts (e.g. the area of natural habitat) and water quality variables (e.g. chlorophyll-a concentration and dissolved oxygen saturation). Our results indicate that log snag placement in estuaries for benefits to fish and fisheries can be maximised if sites are planned strategically.

Flood effects on estuarine fish are mediated by seascape composition and context - Christopher J. Henderson; Andrew D. Olds; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Hayden P. Borland; Ben L. Gilby (Marine Biology, 2024)
Estuaries are crucial feeding, nursery and resting sites for fish but can also be subject to the impacts of severe flooding. The environmental features of estuaries can mediate how they respond to these impacts. For example, the size, configuration, and context of estuarine habitats across seascapes affects the value of patches for fish, and so fish assemblages at sites with a greater habitat extent or closer to the mouth of an estuary may rebound more quickly from flooding. We investigated how a once in 100-year flood event affected fish assemblages at approximately 600 sites across 13 estuaries and six estuarine habitats (bare sediments, log snags, mangrove forests, rocky structures, saltmarsh and seagrass meadows) in southeast Queensland, Australia, and determined whether flood impacts were mediated by the position of sites within the broader estuarine seascape. Sites were surveyed annually in 2020/2021 (pre-flood) and 2022 (6 months post-flood) using underwater videography. Flooding modified the structure of the fish community and reduced the abundance of fish targeted by local fisheries in all six habitats. Crucially, flood effects on fish were greater at sites near more expansive urbanisation in some ecosystems, but lower at sites nearer to the estuary mouth. Maximising the extent of natural habitats across estuaries can mediate the effects of floods and should be priorities for restoration and management plans seeking to maintain biodiversity and fisheries productivity in the face of increasing climate-related disturbances.

Drivers of Ecological Condition Identify Bright Spots and Sites for Management Across Coastal Seascapes - Ben L. Gilby; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Jesse D. Mosman; Andrew D. Olds; Hannah J. Perry (Estuaries and Coasts, 2023)
Disentangling natural and anthropogenic effects on ecosystem condition can uncover bright spots in urban landscapes that are performing above expectations and so are potential sites for conservation or benchmarking, as well as sites performing below expectations that should be the focus of management. In this study, we tested for correlations between metrics indexing ecological condition (focusing on habitat-forming species) and a suite of spatial and environmental variables at 373 sites across four ecosystems (mangroves, seagrass, saltmarsh and rocky outcrops) and 13 estuaries in southeast Queensland, Australia. Ten condition metrics across the four ecosystems correlated with variables indexing the seascape context of sites, with condition metrics typically higher at sites more connected to natural features including the estuary mouth and mangroves. Urbanisation affected only two metrics, with rocky outcrop oyster cover being 75% lower at sites near extensive urbanisation and algae cover being highest at sites with intermediate urbanisation. We identified patterns in at least two variables from each ecosystem, meaning that decisions need to be made regarding optimal ecosystem states. Overall, management sites were more common than bright spots, with 50% more management sites in mangroves, 42.8% more in seagrasses, 38.5% more in saltmarshes and no bright spots in rocky outcrops (however, 10.3% of rocky outcrop sites were bright spots under an alternate ecosystem state model). We found that patterns in habitat condition across coastal seascapes can be predicted using spatial modelling approaches, and that these models can be readily used to prioritise management actions across the entire regions.

Identifying optimal values of coastal habitat condition for management and restoration - Hannah J. Perry; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Andrew D. Olds; Jesse D. Mosman; Ben L. Gilby (Estuarine, Coastal and Shelf Science, 2023)

Salbutamol effects on systemic potassium dynamics during and following intense continuous and intermittent exercise - Muath M. Altarawneh; Aaron Petersen; Robert Smith; David M. Rouffet; Francois Billaut; Ben D. Perry; Victoria L. Wyckelsma; Antony Tobin; Michael J. McKenna (European Journal of Applied Physiology, 2016)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)